Polymer Coatings that Protect Metal Structures from Heat Exposure and their Properties (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
the main content of this article is provided for the creation and application of flame retardant polymer composites to protect structures from thermal impact from Industrial Safety, large-scale scientific research work on the formation of Coke under the influence of thermal temperature, technology to protect compounds from its development, to increase thermal and corrosion tolerance of structures.